The Efforts to Improve Students' Knowledge in Wudu’ Procedure for Elementary School Students Through Modeling The Way Method - Rodiah Rodiah (Universitas Tanjungpura, 2021)
The choice of classroom action research problems was based on the fact that to increase students' knowledge in recognizing the wudu’ procedure was still low. This observation was carried out from July to October 2016. In those months, the students had finished the test semester I and were still at the beginning of the second semester to observe the student's condition from the start. Modeling the Way method was a learning method that helped students found answers on their own based on facts/correct data. Based on important aspects of Modeling the Way method, the role of students was not only to pay attention but also to involve students and teachers in presenting more concrete learning materials. From this research, it can be concluded that with the motivation in learning the method of modeling the way, the knowledge of students in recognizing the wudu’ procedure increases student learning outcomes. The more precise the motivation is given, the more successful the lesson will be. So motivation will always determine the intensity of student learning. It will improve student achievement.